Copper-, ligand- and solvent-free synthesis of ynones by coupling acid chlorides with terminal alkynes - Palimkar, Sanjay S.; Kumar, P. Harish; Jogdand, Nivrutti R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, Kumar V. (Tetrahedron Letters, 2006)
A general and efficient copper-, ligand- and solvent-free synthesis of ynones by coupling of a wide range of acid chlorides with terminal alkynes catalyzed by palladium(II) acetate at room temperature is reported. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ligandless; neat; ynones

Simple and efficient one-pot, three-component, solvent-free synthesis of beta-enaminones via sonogashira coupling-Michael addition sequences - Palimkar, Sanjay S.; More, Vijaykumar S.; Srinivasan, Kumar V. (Synthetic Communications, 2008)
A simple, efficient, and environmentally friendly one-pot, three-component synthesis of beta-enaminones via Sonogashira coupling-Michael addition sequences under solvent-free conditions has been reported. Also the synthesis of beta-enaminones has been achieved in high yields by the direct reaction of amines with ynones under solvent-free conditions.
Keywords: Alkynes; beta-enaminones; coupling; Michael additions; solvent free; ynones

Scandium triflate catalyzed unexpected cleavage of C-C bonds in ynones - Kavthe, Rahul D.; Bansode, Avinash H.; Patil, Nitin T. (Arkivoc, 2016)
An unexpected C-C bond cleavage in ynones in the presence of catalytic amounts of Sc(OTf)(3) in methanol under microwave irradiation has been discussed. The effect of substituent on the regioselectivity of C-C bond cleavage has carefully been addressed by employing various ynones derivatives. The mechanism has been proposed for the observed regioselectivity.
Keywords: C-C bond cleavage; Esters; Ketones; scandium triflate; ynones